Sustainability Communication Strategies by Women Coffeepreneurs in Toraja - Riu, Isma Azis (Malaqbi Publisher, 2025)
This study examines how women coffee entrepreneurs (coffeepreneurs) in Toraja, Indonesia, communicate sustainability practices within their unique socio-cultural context. Using a qualitative case study approach, the research engaged fifteen women coffeepreneurs through in-depth interviews, participant observation, and analysis of textual artifacts to understand their narrative strategies, channel selection, and negotiation of gendered constraints. Findings reveal that these women employ three key communicative practices: (1) cultural anchoring of sustainability messages through ancestral stewardship narratives and moral idioms; (2) multimodal bricolage combining oral traditions, digital platforms, and community networks; and (3) strategic storytelling that leverages care-based expertise to assert authority in male-dominated spaces. The study identifies significant tensions between affective storytelling and market demands for verifiable claims, highlighting how digital platforms both amplify and complicate sustainability communication. Results underscore the importance of co-designed capacity-building programs that enhance communicative competencies while respecting cultural frameworks. The research concludes that supporting women’s communicative agency requires hybrid approaches that integrate culturally resonant narratives with accessible verification mechanisms, ultimately contributing to more equitable and sustainable value chains.